Using enzymatic hydrolyzate as new nitrogen source for L-tryptophan fermentation by E.coli. Issue 1 (1st January 2020) - Xu, Da; Zhang, Zhen; Liu, Ziqiang; Xu, Qingyang
ABSTRACT: This study presents new methods for hydrolyzing bacterial cell in cyclic utilization of waste bacterial cell for L-tryptophan production by fermentation. Using enzymatic hydrolysis of the pre-treated bacterial cells which were collected from an L-tryptophan fermentation broth, trypsin was selected as the optimal protease for hydrolyzing the bacterial cell. The optimum conditions for hydrolysis were determined by the orthogonal test. Hydrolyzate was then dealt with a compound protease to further increase its content of free amino acids. With the optimum conditions of pH = 8, temperature of 37°C, treatment time of 6 h, and E/S of 4%, the final content of free amino acids in the hydrolyzate was 500.61 mg/g. The hydrolyzate and the yeast extract were added to the medium at the proportion of 1:1, which served as an organic nitrogen source for L-tryptophan production by fermentation. The production of L-tryptophan was 53.87 g/L, and the highest biomass was 53.45 g/L. As an organic nitrogen source, this hydrolyzate satisfies the requirements for L-tryptophan production by fermentation. Graphical abstract: